1999
DOI: 10.1046/j.1460-2695.1999.00202.x
|View full text |Cite
|
Sign up to set email alerts
|

A Weibull stress model to predict cleavage fracture in plates containing surface cracks

Abstract: This study applies recent advances in probabilistic modelling of cleavage fracture to predict the measured fracture behaviour of surface crack plates fabricated from an A515‐70 pressure vessel steel. Modifications of the conventional, two‐parameter Weibull stress model introduce a non‐zero, threshold parameter (σw‐min ). The introduction of σw‐min brings numerical predictions of scatter in toughness data into better agreement with experimental measurements, and calibration of this new parameter requires no add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(36 citation statements)
references
References 21 publications
1
26
0
Order By: Relevance
“…Bakker and Koers 1991;Xia and Cheng 1997). Gao et al (1999) have proposed a modified expression given by:…”
Section: Statistical Models For Cleavage Fracture-beremin Modelmentioning
confidence: 99%
“…Bakker and Koers 1991;Xia and Cheng 1997). Gao et al (1999) have proposed a modified expression given by:…”
Section: Statistical Models For Cleavage Fracture-beremin Modelmentioning
confidence: 99%
“…The applicability of this distribution to quasibrittle materials has been questioned by some authors and deviations from the Weibull statistics have been observed [80][81][82][83]. Strictly speaking, there are no cracks in our system, and stress concentration is a consequence of cell-induced disorder.…”
Section: Scale Dependencementioning
confidence: 99%
“…The next section describes numerical analyses for fracture specimens extracted from an A515-70 pressure vessel and an API X80 pipeline steel weld that were tested in the experimental program. Gao et al (1999) describes the uniaxial stress-strain curve for the A515-70 pressure vessel steel at the test temperature, 2 J 7 − = T°C and °C. Minami et al (1995) provides the uniaxial true stress vs. logarithm strain curves for the API X80 pipeline steel (base plate and overmatch weld material) at the test temperature, 28 − = T 5 − = T°C.…”
Section: Materials Models and Computational Proceduresmentioning
confidence: 99%
“…The research code WSTRESS (Ruggieri, 2001 ). Gao et al (1999) provides the true stress-logarithmic strain curve at the test temperatures (°C and °C) for this material used in the finite element analyses of the specimens.…”
Section: Materials Models and Computational Proceduresmentioning
confidence: 99%